2008
DOI: 10.3200/joer.101.3.158-176
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies Teachers' Conceptions of History: Calling on Historiography

Abstract: In this qualitative research study, the author investigated social studies teachers' conceptions of history by conducting in-depth, semistructured interviews with 12 in-service teachers. Results indicated that participants tended to look at the outcome of historical knowledge construction without considering its process or mentioning forces that shape historical writing. Rather than considering the whole relationship or interplay between the past, the recorded past, and the historian, participants observed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
28

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 82 publications
5
44
0
28
Order By: Relevance
“…On the other hand, those individuals who believe that knowledge is complex and interrelated may assess historical events in consideration with their multi-dimensional characteristics and inter-relatedness. Examining social studies teachers' conceptions of history, Yılmaz (2008) found that teachers with naive epistemological beliefs regard historical knowledge as objective facts. Kösemen and Şahin (2014) studied social studies teachers' views on social studies curriculum and compared those viewpoints with their epistemological beliefs.…”
mentioning
confidence: 99%
“…On the other hand, those individuals who believe that knowledge is complex and interrelated may assess historical events in consideration with their multi-dimensional characteristics and inter-relatedness. Examining social studies teachers' conceptions of history, Yılmaz (2008) found that teachers with naive epistemological beliefs regard historical knowledge as objective facts. Kösemen and Şahin (2014) studied social studies teachers' views on social studies curriculum and compared those viewpoints with their epistemological beliefs.…”
mentioning
confidence: 99%
“…Next to this, the results suggest that part of the differences in teachers' performance might be related to their training prior to the start of their career (McDiarmid, 1994;Yilmaz, 2010). More specifically, it was found that all 9 teachers with an integral approach held a master degree of a training program that had introduced them to academic history (with the exception of teacher 19, who had followed a political sciences program).…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that even teachers with a deep understanding of how historical knowledge is constructed, may choose not share this knowledge with their students, because doing so runs counter to their beliefs about school history (Barton & Levstik, 2003;McDiarmid, 1994). Even so, others have argued that history teachers should have a basic understanding of inquiry methods, if they are to support their students during classroom inquiries (Martin & MonteSano, 2008;Yilmaz, 2010). Unfortunately, there is not much information available about the extent to which teachers know how to conduct a historical inquiry.…”
Section: History Teachers' Knowledge Of Inquiry Methodsmentioning
confidence: 99%
“…The debate in the literature concerning changing teachers' practice in the history classroom suggested an approach which included more disciplinary knowledge (Yilmaz, 2008;Fellace, 2009;Parkes, 2011) and one which encompassed a bigger purpose to the teaching history in the classroom, where "students should Yesterday&Today, No. 16, December 2016 learn history to contribute to a participatory, pluralistic democracy" (Barton & Levstik, 2004:259).…”
Section: Implications For a History Methodology Coursementioning
confidence: 99%
“…preservice teachers to the disciplinary underpinnings of history (Yilmaz, 2008;Fellace, 2009;Parkes, 2011). In this article, I argue that reviewing an oral history assignment, based on a topic such as "Life before and after 1994 in South Africa", has the potential to develop a more in-depth understanding of the discipline with preservice teachers.…”
Section: Introductionmentioning
confidence: 99%